Tropical Cowboys : Westerns, Violence, and Masculinity in Kinshasa - Gondola, Ch. Didier, 1966- (Book collections on Project MUSE., 2016)
During the 1950s and 60s in the Congo city of Kinshasa, there emerged young urban male gangs known as "Bills" or "Yankees." Modeling themselves on the images of the iconic American cowboy from Hollywood film, the "Bills" sought to negotiate lives lived under oppressive economic, social, and political conditions. They developed their own style, subculture, and slang and as Ch. Didier Gondola shows, engaged in a quest for manhood through bodybuilding, marijuana, violent sexual behavior, and other transgressive acts. Gondola argues that this street culture became a backdrop for Congo-Zaire's emergence as an independent nation and continues to exert powerful influence on the country's urban youth culture today